The outlook for China's fossil fuel consumption under the energy transition and its geopolitical implications - Michal Meidan (The Oxford Institute for Energy Studies, 2023)
China is currently the world's largest oil importer and is on track to becoming the biggest consumer of liquefied natural gas (LNG). This dependency is viewed as a strategic vulnerability, especially as China's ties with the USA are worsening and Beijing has growing concerns about Washington's use of sanctions. As China pursues its low carbon energy transition, will reduced consumption of oil and gas shape its views of energy security and its geopolitical relations with producer countries? This paper discusses different scenarios for China's oil and gas consumption, and notes that even though the overall demand volumes vary quite widely between outlooks, China is set to remain the world's largest consumer of oil and the second largest importer of gas (behind the EU) for decades to come. It argues that given the dominance of coal and increasingly of renewables in the country's energy mix, the economic impact of oil and gas supply outages is limited and will decline further. Nonetheless, China's sense of energy insecurity will be informed as much by Beijing's perceptions as by market realities. Looking ahead, the number of oil and gas suppliers to China is set to shrink, with imports coming predominantly from the USA, Russia, and the Middle East (and most notably Saudi Arabia for oil, and Qatar for LNG). But just as China will become increasingly dependent on a small number of exporters, their interdependence will deepen, leading producers to compete for market share in China. The dependence on a smaller number of suppliers could be seen as a vulnerability, but it also gives Beijing geopolitical leverage. The paper analyses the importance of oil and gas in China's relations with its main suppliers, and argues that as China has incorporated energy interests into its broader foreign policy objectives, given the ongoing need for critical materials and other commodities (metals and grains, for instance), China will likely remain invested in countries and regions even after its oil and gas imports from them fall. Finally, the paper argues that China's energy security policies are increasingly being shaped by the prospect of sanctions. Beijing will want to deepen ties and build coalitions aimed at weakening the USA's ability to contain and suppress China. Beijing will also want to consolidate its relations with energy suppliers (as well as suppliers of other raw materials) so that, in the event of sanctions or a conflict, suppliers will struggle to pick between the USA and China, or will opt to align with China.
Keywords: 330; China; Coal; critical materials; energy security; Gas; Geopolitics; LNG; low carbon transition; Middle East; net-zero; Oil; Renewables; Russia; Saudi Arabia; Supply Chains; USA